Poder e comunicação: a emergência do marketing na política capixaba da década de oitenta (1980) - Macedo, Maria Helena de Almeida (2007)
This study analyses the close relationship that exists in the present time between power, politics, and communication, with focus on the history of political marketing in the state of Espírito Santo in general, and, in particular, the work of journalists – actors who have dominated this social arena since the 1980s, when practices other that the traditional ones emerged in the political setting of Espírito Santo. It also discusses the mechanisms and strategies the professionals of communication have used to penetrate and interfere in the political processes while acquiring power themselves in this context. In order to do so, this paper goes back to the origins of political marketing in Espírito Santo, and follows it during its growth and consolidation. It also follows the holders of political power for two decades in order to identify how they relate to the unrevealed power behind the scenes and the communication strategies prevailing in the society of the spectacle, where appearances rule.